Enantioselective Total Syntheses of Pallambins A–D. Issue 38 (7th August 2019) - Zhang, Xiwu; Cai, Xinxian; Huang, Bin; Guo, Lei; Gao, Zhongrun; Jia, Yanxing
Abstract: The first enantioselective total syntheses of (−)‐pallambins A–D have been achieved in 15 or 16 steps from a known chiral cyclohexenone. Salient features of the syntheses include a palladium‐catalyzed oxidative cyclization to assemble the [3.2.1]bicyclic moiety, an Eschenmoser–Claisen rearrangement/lactone formation sequence to construct the C ring, an intramolecular Wittig reaction to form the D ring, and individual transformations of pallambins C and D to generate pallambins A and B. The described synthesis avoids protecting‐group manipulations through the design of highly chemo‐ and stereoselective transformations. During the course of this work, a palladium‐catalyzed method for the dehydrobromination of α‐bromoketones was developed, and the scope of this transformation was also investigated. Abstract : No protection needed : The first enantioselective total syntheses of pallambins A–D were achieved without the use of protecting groups. A salient feature of these syntheses is the formation of three rings in three cyclizations. A palladium‐catalyzed process for the dehydrobromination of α‐bromoketones was also developed.